2018
DOI: 10.1139/apnm-2017-0597
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing sprint duration from 20 to 10 s during reduced-exertion high-intensity interval training (REHIT) attenuates the increase in maximal aerobic capacity but has no effect on affective and perceptual responses

Abstract: Purpose: Recent studies have demonstrated that modifying the 'classic' 6x30-s 'all-out' sprint interval training (SIT) protocol by incorporating either shorter sprints (6x10-s or 15-s sprints) or fewer sprints (e.g. 2x20-s sprints; reduced-exertion high-intensity interval training (REHIT)) does not attenuate the training-induced improvements in maximal aerobic capacity (VȮ2max). The aim of the present study was to determine whether reducing the sprint duration in the REHIT protocol from 20 s to 10 s per sprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 42 publications
7
35
1
Order By: Relevance
“…They reported that affective valence decreased progressively (by ~1 point on the feeling scale) with each 'all-out' 20-s sprint and, in contrast to our findings, that REHIT was associated with more negative affective valence compared with MICT (Stork et al, 2018). The more negative affective response with REHIT reported in their study can be explained by: 1) the incorporation of the third sprint (which is unnecessary for achieving improvements in cardiometabolic risk factors (Metcalfe et al, 2012;Nalçakan et al, 2018;), and 2) the lack of sufficient familiarisation with REHIT prior to the main experiment. In our REHIT training studies (Metcalfe et al, 2012;Nalçakan et al, 2018), we have observed that progressively increasing sprint duration from 10 s to 20 s over the first few sessions completely prevents the feelings of nausea which were reported in early studies of 'classic' SIT.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…They reported that affective valence decreased progressively (by ~1 point on the feeling scale) with each 'all-out' 20-s sprint and, in contrast to our findings, that REHIT was associated with more negative affective valence compared with MICT (Stork et al, 2018). The more negative affective response with REHIT reported in their study can be explained by: 1) the incorporation of the third sprint (which is unnecessary for achieving improvements in cardiometabolic risk factors (Metcalfe et al, 2012;Nalçakan et al, 2018;), and 2) the lack of sufficient familiarisation with REHIT prior to the main experiment. In our REHIT training studies (Metcalfe et al, 2012;Nalçakan et al, 2018), we have observed that progressively increasing sprint duration from 10 s to 20 s over the first few sessions completely prevents the feelings of nausea which were reported in early studies of 'classic' SIT.…”
Section: Discussioncontrasting
confidence: 91%
“…The more negative affective response with REHIT reported in their study can be explained by: 1) the incorporation of the third sprint (which is unnecessary for achieving improvements in cardiometabolic risk factors (Metcalfe et al, 2012;Nalçakan et al, 2018;), and 2) the lack of sufficient familiarisation with REHIT prior to the main experiment. In our REHIT training studies (Metcalfe et al, 2012;Nalçakan et al, 2018), we have observed that progressively increasing sprint duration from 10 s to 20 s over the first few sessions completely prevents the feelings of nausea which were reported in early studies of 'classic' SIT. Therefore, in the present study we included three familiarisation sessions with participants performed increasing duration of allout sprints during each.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations